1998
DOI: 10.1021/bi980511m
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Transmembrane H+-Transporting Subunit c of the F1Fo ATP Synthase

Abstract: Subunit c is the H+-translocating component of the F1F0 ATP synthase complex. H+ transport is coupled to conformational changes that ultimately lead to ATP synthesis by the enzyme. The properties of the monomeric subunit in a single-phase solution of chloroform-methanol-water (4:4:1) have been shown to mimic those of the protein in the native complex. Triple resonance NMR experiments were used to determine the complete structure of monomeric subunit c in this solvent mixture. The structure of the protein was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
215
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(230 citation statements)
references
References 54 publications
(85 reference statements)
15
215
0
Order By: Relevance
“…Therefore, it is reasonable to presume that they would also be favorable within the setting of the NHE1 protein. Indeed, a number of studies have demonstrated strong correspondence between structures of peptides or protein segments obtained in membrane mimetic solvents to structures obtained by solution state NMR in micelles or to entire membrane proteins determined by x-ray crystallography (11)(12)(13). Most interestingly, we find that CD 3 OH:CDCl 3 :H 2 O provides a well defined peptide structure, whereas the peptide in Me 2 SO appears much less structured.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Therefore, it is reasonable to presume that they would also be favorable within the setting of the NHE1 protein. Indeed, a number of studies have demonstrated strong correspondence between structures of peptides or protein segments obtained in membrane mimetic solvents to structures obtained by solution state NMR in micelles or to entire membrane proteins determined by x-ray crystallography (11)(12)(13). Most interestingly, we find that CD 3 OH:CDCl 3 :H 2 O provides a well defined peptide structure, whereas the peptide in Me 2 SO appears much less structured.…”
Section: Discussionsupporting
confidence: 50%
“…This provides insight into structured regions, in our case, without fixing the segment as a whole into a single conformation. The use of solution conditions having a low dielectric constant to mimic a membrane environment has become quite common for structural studies of transmembrane proteins or peptides and has provided structures of isolated protein segments consistent with their structures in the full protein (11)(12)(13). Our study demonstrates that whereas TM IV is structured, only a 4 -6-residue stretch of the segment is helical.…”
mentioning
confidence: 52%
“…Helix I comprises residues L5 to I26, and helix II comprises the segment G29 to N82 with a short interruption between Q46 and P47. In particular no signal intensities were obtained for the a helix characteristic connectivities d aN (23,26), d ab (23,27), d aN (24,27), d ad (24,28), d aN (25,29), d ab (25,28), d ad (25,28) and d aN (26,30). The interruption between helix I and helix II is further confirmed by the small 13 C a downfield chemical shift deviation of the segment A24 to G29.…”
Section: Secondary Structure and Global Foldmentioning
confidence: 95%
“…The b subunit is a long helical protein whose aminoterminal is embedded in the membrane, and its carboxyl terminus interacts with a and d at the top of F 1 (Fillingame et al 2000). The structure of the c subunit, two transmembrane a-helices connected by a polar loop, has been solved by NMR (Girvin et al 1998). Low-resolution electron (Birkenhäger et al 1990) and atomic force microscopy (AFM; Singh et al 1996;Takeyasu et al 1996) suggested a ring structure formed from multiple c subunits.…”
Section: Catalysis Transport and Energy Coupling By F-atpases (A)mentioning
confidence: 99%